Anti‐activated factor II assay for monitoring unfractionated heparin in children: results of the HEARTCAT study. (25th November 2016) - Hanslik, A.; Kitzmüller, E.; Tran, U. S.; Thom, K.; Karapetian, H.; Prutsch, N.; Voitl, J.; Michel‐Behnke, I.; Newall, F.; Male, C.
Abstract : Essentials Unfractionated heparin has variable effects in children and therefore, monitoring is essential. A randomized controlled trial substudy investigating an anti‐IIa assay in children was conducted. Anti‐IIa values are lower in younger children, an effect more pronounced at low‐dose heparin. Heparin effect on Xa and IIa is not equal, particularly in infants and after high‐dose heparin. Summary: Background: Unfractionated heparin (UFH) is used for the prophylaxis and treatment of thrombosis in children. Laboratory monitoring of UFH is needed to prevent over‐anticoagulation or under‐anticoagulation. Objectives: To investigate the association between UFH dose and UFH effect as monitored with the anti‐activated factor II (FIIa) assay, the relationship between anti‐FIIa and anti‐activated factor X (FXa) effects, and the influence of patient age and other factors on UFH effect. Patients and methods: This was a randomized controlled trial in children during cardiac catheterization, comparing high‐dose UFH (100 units kg −1 bolus) with low‐dose UFH (50 units kg −1 bolus). Blood samples were drawn at baseline, and after 30 min, 60 min, and 90 min. For the purpose of this study, 49 children and 117 blood samples were evaluated. Results: The anti‐FIIa assay discriminated well between high‐dose and low‐dose UFH. Multiple regression demonstrated significant influences of UFH dose and age on anti‐FIIa levels. Younger children had lower anti‐FIIa levels than older children, an effect that was more pronounced with low‐dose UFH. Anti‐FXa/anti‐FIIa ratios were equal with low‐dose UFH. However, anti‐FXa levels were relatively increased over anti‐FIIa levels in infants and after high‐dose UFH bolus administration. Conclusion: The UFH effect on anti‐FIIa levels is lower in infants than in older children. This influence of age appears to be dose‐dependent, being more pronounced with low‐dose UFH. Anti‐FXa and anti‐FIIa levels are not equal, particularly in infants and after high‐dose UFH. Monitoring UFH solely with anti‐FXa assays may not be sufficient in children, and the anti‐FIIa assay may provide important complementary information.